The Value of Environmental Care in Islamic and Catholic Religious Education Subjects (Study of the Syllabus and Strategy of Religious Education Teachers in Implementing Environmental Care Values) - Hidayatulloh, Ahmad Noor Muhib (International Journal on Advanced Science, Education, and Religion, 2025)
The background of this study was the lack of environmental concern both from the internal and external factors. Thus, education has an important role in building better civilizations through environmental values. Teachers are students’ exemplary centers at school, especially the religious study teachers who have additional responsibility to foster students’ morals which are in accordance with the noble ideas taught in a religion. Therefore, the aim of this study is to figure out how far the syllabus in Islamic and Catholic Religious Studies are developed to suit teachers’ strategies in implementing Environmental Care values to the students of SMPN 6 Salatiga. Qualitative methods using interviews, observations and document reviews, especially for the religious studies syllabus, were carried out. The examined variables show that the syllabus of religious study subjects was developed by the teachers, especially for the materials or discussion topics which are relevant to the review from theological and psychological aspects. According to the religious study teachers, syllabus development can be concluded by the similarities in the context of environmental care values which provide understanding about environmental care behavior as one of the characteristics of believers which also have humanity. Those factors become part of spiritual, emotional and intellectual intelligence. The development of religious study syllabus with the topic of environmental care is strongly affected by the doctrine and belief of each religion.